2018
DOI: 10.1016/j.drugalcdep.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Tapering off and returning to buprenorphine maintenance in a primary care Office Based Addiction Treatment (OBAT) program

Abstract: Despite the fact that many patients desire to discontinue buprenorphine, a minority had a documented taper. Among those who tapered, more than half did so unsupervised by the clinic and a majority of those who tapered off returned to buprenorphine treatment within two years. As many patients are unable to successfully taper off buprenorphine, the medical community must work to address any barriers to long-term maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Typical reasons were “my life has never been this stable—I don’t want to rock the boat,” “I don’t think it will work,” “I’m scared,” and “I’ve tried before and started using again.” While only 16% (n = 45) of the patients attempted buprenorphine taper, the success of this group was remarkable. Their 91% (n = 41) success rate in remaining off of opioids through the end of the study is significantly higher than other reported studies 8,9,26‐28 . This much higher success rate is likely related to allowing the decision to taper to be totally voluntary, as well as the length of taper.…”
Section: Discussionmentioning
confidence: 64%
“…Typical reasons were “my life has never been this stable—I don’t want to rock the boat,” “I don’t think it will work,” “I’m scared,” and “I’ve tried before and started using again.” While only 16% (n = 45) of the patients attempted buprenorphine taper, the success of this group was remarkable. Their 91% (n = 41) success rate in remaining off of opioids through the end of the study is significantly higher than other reported studies 8,9,26‐28 . This much higher success rate is likely related to allowing the decision to taper to be totally voluntary, as well as the length of taper.…”
Section: Discussionmentioning
confidence: 64%
“…Only a small minority of individuals in long-term buprenorphine treatment successfully taper off 40 . In contrast, only 15% of our sample was planning to stay on buprenorphine indefinitely, leaving a large group of people taking buprenorphine who will eventually consider and seek support in coming off their medication.…”
Section: Discussionmentioning
confidence: 99%
“…4 Providing a safe and anonymous space for users is at the core of Reddit's design and culture, with elaborate community-established rules and etiquettes known as 'rediquette'. 5 Due to the emphasis on anonymity of this platform, it is particularly popular for openly discussing sensitive and stigmatized topics, such as opioid addiction and recovery.…”
Section: Data Collection Strategies For Initial Analysesmentioning
confidence: 99%
“…One study looked at 28-day vs 56-day tapering schedule in adolescents with OUD and found more opioid-free urines and more sustained retention in treatment with the longer tapering regimen (4). Another 12-year retrospective study of 1308 patients on buprenorphine showed that an estimated 15% tapered off buprenorphine, fewer than half of whom were medically supervised (5). Package insert information for the commonly used sublingual buprenorphine formulations do not include tapering advice and, in fact, may specifically advise against cutting, chewing, or swallowing the strips, all methods that patients structuring their own buprenorphine tapers commonly use (6).…”
Section: Introductionmentioning
confidence: 99%